ANALISIS ORIENTASI PELUANG DAN FOKUS PADA PELANGGAN DALAM MENINGKATKAN KEPUASAN KONSUMEN (STUDI KRESNA KAMPUNG INGGRIS PARE) - Nasution, Muhammad Fajar Padlin; Pandiangan, Bilson; br Sinulingga, Nora (Journal Business and Management, 2025)
This study aims to examine the application of opportunity orientation and customer focus on customer satisfaction at Kresna, Kampung Inggris Pare. This study is a descriptive quantitative study, which uses an online survey via Google Forms to collect data and obtained a total of 121 student respondents. The data analysis method used is multiple linear regression analysis. The results of the analysis show that opportunity orientation has a positive and significant effect on customer satisfaction. Customer focus has a positive and significant effect on customer satisfaction. Simultaneously, opportunity orientation and customer focus have a positive and significant effect on customer satisfaction, with a contribution of 61.1%.